Long-term correction of hemophilia A via integration of a functionally enhanced FVIII gene into the AAVS1 locus by nickase in patient-derived iPSCs - Do-Hun Kim; Sang-Hwi Choi; Jin Jea Sung; Sieun Kim; Hanui Yi; Sanghyun Park; Chan Wook Park; Young Woo Oh; Jungil Lee; Dae-Sung Kim; Jong-Hoon Kim; Chul-Yong Park; et al. (Experimental and Molecular Medicine)
Abstract Hemophilia A (HA) is caused by mutations in coagulation factor VIII (FVIII). Genome editing in conjunction with patient-derived induced pluripotent stem cells (iPSCs) is a promising cell therapy strategy, as it replaces dysfunctional proteins resulting from genetic mutations with normal proteins. However, the low expression level and short half-life of FVIII still remain significant limiting factors in the efficacy of these approaches in HA. Here, we constructed a functionally enhanced FVIII variant, F309S/E1984V-mutated B domain-deleted (BDD)-FVIII (FE-FVIII), with increased activity and stability. We inserted FE-FVIII with a human elongation factor-1 alpha (EF1α) promoter into the AAVS1 locus of HA patient-derived iPSCs via CRISPR/Cas9 (D10A) nickase to ensure expression in any cell type. FE-FVIII was expressed not only in undifferentiated FE-FVIII-inserted (FE-KI) iPSCs but also in endothelial cells (ECs) differentiated from them in vitro. Compared with mice transplanted with wild-type BDD-FVIII-containing ECs, immunocompetent HA mice intravenously transplanted with FE-KI ECs presented a 2.12-fold increase in FVIII activity in the blood and an approximately 20% greater survival rate after hemorrhagic tail injury. For sustained efficacy, FE-KI ECs were subcutaneously transplanted into immunodeficient HA mice, resulting in amelioration of the hemophilia phenotype for more than 3 months. This strategy can improve FVIII function and may provide a universal therapeutic approach for treating HA.